Optimal acupuncture methods for lower limb motor dysfunction after stroke: a systematic review and network meta-analysis - Liu, Yaning; Tang, Yuqi; Wang, Linjia; Yu, Pei; Wang, Can; Zeng, Lichuan; Yuan, Jing; Zhao, Ling (Frontiers in Neurology, 2024)
Background The lower limb motor dysfunction caused by stroke is one of the main sequelae affecting patients’ ability to live normally in the later period. Acupuncture treatment of limb movement dysfunction after stroke has been recommended by authoritative guidelines for reducing limb spasticity, enhancing limb strength and so on. However, the efficacy of different acupuncture methods in treating lower limb motor dysfunction after stroke remains controversial. Objective In this paper, network meta-analysis (NMA) was used to prioritize various acupuncture intervention combinations commonly used in clinical practice, try to screen the acupuncture intervention scheme with the highest clinical efficacy and safety, and explore its rationality in guiding clinical practice. Methods We searched a total of 4,312 studies from 8 databases and 2 clinical trial registries, and selected 43 articles for systematic review. We used pairwise meta-analysis and network meta-analysis to evaluate the efficacy and ranking of various acupuncture interventions. At the same time, the risk of bias, publication bias, and sensitivity of included randomized controlled trials were analyzed. The main outcome indicator was Fugl-Meyer assessment of lower extremity (FMA-LE), and the secondary outcome indicators were Modified Barthel Index (MBI), Berg balance scale (BBS) and Modified Ashworth scale (MAS). Results A total of 4,134 patients in 43 studies were included. The intervention included 9 acupuncture-related treatments, of which 20.9% were classified as high-risk. Among the four outcome indicators in pairwise meta-analysis, the effect of body acupuncture combined with conventional rehabilitation has the highest comprehensive credibility in terms of efficacy and safety comparing with conventional rehabilitation [SMD = 1.14, 95%CI (0.81, 1.46)], [SMD = 1.35, 95%CI (0.97, 1.72)], [SMD = 1.22, 95%CI (0.39, 2.05)], [SMD = 1.21, 95%CI (0.74, 1.44)]. In addition, multiple intervention methods, for example, warm acupuncture plus rehabilitation treatment for MBI and electroacupuncture plus body acupuncture plus rehabilitation treatment for BBS, may increase certain additional effects on different outcome indicators. Conclusion This study proves that body acupuncture combined with rehabilitation treatment is the most widely used intervention method with the highest evidence quality in the treatment of lower limb motor dysfunction after stroke. However, for some other acupuncture methods, large samples and high-quality clinical randomized controlled trials are still needed to be fully verified.